Analysis of College Students’ Entrepreneurship Education and Entrepreneurial Psychological Quality From the Perspective of Ideological and Political Education - Jin, Yuqian (Frontiers in Psychology, 2022)
The purpose is to meet the needs of social development, encourage college students’ employability, and alleviate social pressure. First, the domestic and international employment situation is discussed along with the derivation of entrepreneurship education. Second, ideological and political education is summarized, and accordingly, its internal advantages and external conditions are explained. Then, the current situation and existing problems of entrepreneurship education in Chinese higher education institutions are analyzed from the perspectives of entrepreneurship ideology, entrepreneurship thinking, and entrepreneurship ability. Consequently, a proposal is put forward to integrate entrepreneurship education into ideological and political education to promote the coordinated development of the multidisciplinary course. Finally, the QS (Questionnaire Survey) is designed on the relationship between college students' entrepreneurship education and ideological and political education, and the QS is conducted from three aspects: college students' entrepreneurship views, suggestions, and cognition of the ideological and political education. The QS results show that less than 10% of students are very interested in entrepreneurship education, and most students believe that entrepreneurship education plays a very limited role in their growth. Additionally, classroom teaching accounts for the most in entrepreneurship education, while extracurricular practice accounts for only 15%. In terms of teaching content, 80% of students believe that teachers of professional courses have made outstanding contributions to teaching results, but the number of teachers of professional courses is the least among all teachers. Further, the satisfaction of entrepreneurship education among college students is analyzed through the QS by issuing to three local higher education institutions, finding that the college students’ understanding of entrepreneurship education is incomplete. The advantages of ideological and political education should be fully exerted to improve the recognition of entrepreneurship education, and entrepreneurship education should be integrated into daily teaching content. In this way, entrepreneurship education and ideological and political education can be fused, and entrepreneurship education can promote students' entrepreneurial ability and entrepreneurial thinking.